Evaluasi Pengelolaan Lansekap Taman Kota Bendosari, Salatiga - Kristiyanto, Yuli; Pudjihartati, Endang (Jurnal Arsitektur Lansekap, 2023)
Evaluation of the Management Landscape in Bendosari City Park, Salatiga . Bendosari City Park is a city park located in Salatiga, Central Java. This City Park is one of the Green Open Spaces located on the side of the highway, has an area of 3.8 ha, of course requires maximum maintenance because there are two landscape elements in the park, hardscape elements there are buildings and public facilities for park visitors, while softscape elements there are vegetation in the form of trees dominating so as to make the atmosphere cool. The purpose of this research is to determine the existing conditions and landscape management of the park, then the characteristics and satisfaction level of visitors, so that an analysis of strength and weakness, opportunities, and threats of city park landscape management can be carried out, then produce recommendations for city park landscape management strategies based on the results of SWOT analysis. Therefore, we evaluated the landscaping management of Bendosari City Park using the SWOT method. Having the strength of the location with the highway, the weakness is the lack of experts who understand the maintenance of softscapes, the opportunities is the support from the city government, and the threats that have a lack of awareness of visitors about the cleanliness of the park, then the preparation of management strategies that can be recommended, such as maximizing the use of city parks as green open space by improving management that already exists, and draws up in writing the duties and responsibilities of the gardener to make it easier to understand.